Molecular engineering of conjugated organic molecule and carbon nanotube assemblies - a linear and nonlinear spectroscopic study - Ní Mhuircheartaigh, Éimhín Máire Caitríona (Trinity College (Dublin, Ireland). School of Physics, 2007)
Single walled carbon nanotubes (SWNTs) possess unique structural, mechanical and electronic properties, and are thus promising materials for a host of future applications. However, their potential is limited in that they are insoluble in aqueous and organic solutions and satisfactory control over nanotube location and orientation has yet to be achieved. SWNT solubility has recently been achieved by functionalizing them covalently and noncovalently. Non- covalent functionalization is of particular interest as it provides a method of handling the nanotubes chemically without altering the electronic structure of the SWNT themselves.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin